Soil acid Management using Biochar: Review - Miheretu Bedassa (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Soil acidity affects the growth of crops because acidic soil contain toxic levels of aluminum and manganese and characterized by deficiency of essential plant nutrients such as P, N, K, Ca, Mg, and Mo. The management options to correct acid soils are, improve nutrient use efficiency, liming, application of organic materials, biocha, appropriate crop rotations, crop mixtures, use of varieties that tolerant to Al and Mn toxicity. Biochar application improves crop productivity through enhancing water holding capacity, cation exchange capacity (CEC), adsorption of plant nutrients and creates suitable condition for soil micro-organisms.